The longer term refinancing operations of the ECB - Tobias Linzert; Dieter Nautz; Ulrich Bindseil (European Central Bank (ECB), 2004)
This paper employs individual bidding data to analyze the empirical performance of the longer term re?nancing operations (LTROs) of the European Central Bank (ECB). We investigate how banks' bidding behavior is related to a series of exogenous variables such as collateral costs, interest rate expectations, market volatility and to individual bank characteristics like country of origin, size and experience. Panel regressions reveal that a bank's bidding depends on bank characteristics. Yet, different bidding behavior generally does not translate into differences concerning bidder success. In contrast to the ECB's main re?nancing operations, we ?nd evidence for the winner's curse effect in LTROs. Our results indicate that LTROs do neither lead to market distortions nor to unfair auction outcomes.
Keywords: E52; D44; 330; Auctions; Monetary Policy Instruments ECB; Winner's Curse